Juxtaposing Sonare and Videre Midst Curricular Spaces: Negotiating Muslim, Female Identities in the Discursive Spaces of Schooling and Visual Media Cultures - Watt, Diane P. (Université d'Ottawa / University of Ottawa, 2011)
Muslims have the starring role in the mass media’s curriculum on otherness, which circulates in-between local and global contexts to powerfully constitute subjectivities. This study inquires into what it is like to be a female, Muslim student in Ontario, in this post 9/11 discursive context. Seven young Muslim women share stories of their high schooling experiences and their sense of identity in interviews and focus group sessions. They also respond to images of Muslim females in the print media, offering perspectives on the intersections of visual media discourses with their lived experience. This interdisciplinary project draws from cultural studies, postcolonial feminist theory, and post-reconceptualist curriculum theorizing. Working with auto/ethno/graphy, my own subjectivity is also brought into the study to trouble researcher-as-knower and acknowledge that personal histories are implicated in larger social, cultural, and historical processes. Using bricolage, I compose a hybrid text with multiple layers of meaning by juxtapositing theory, image, and narrative, leaving spaces for the reader’s own biography to become entangled with what is emerging in the text. Issues raised include veiling obsession, Islamophobia, absences in the school curriculum, and mass media as curriculum. Muslim females navigate a complex discursive terrain and their identity negotiations are varied. These include creating Muslim spaces in their schools, wearing hijab to assert their Muslim identity, and downplaying their religious identity at school. I argue for the need to engage students and teacher candidates in complicated conversations on difference via auto/ethno/graphy, pedagogies of tension, and epistemologies of doubt. Educators and researchers might also consider the possibilities of linking visual media literacy with social justice issues.
Keywords: border epistemologies; bricolage; autoethnography; cultural studies; curriculum theory; epistemologies of doubt; feminist postcolonial theory; high schooling experiences post 9/11; mass media as educator; media literacy and social justice issues; Muslim female student identities; visual media literacy; media representations of Muslim women; decolonizing methodology; experimental ethnography; intercultural education; in-between sonare and videre; currere; hybrid consciousness; deconstructive pedagogies; complicating readings of self and other; entanglement in veiling discourses; post-reconceptualist curriculum theorizing; disrupting Orientalism; photographs, culture, and memory; relational theories of learning; feminist poststructural critique; personal narratives